الوصفُ في الرواية العربية الحديثة رواية متاهة الأولياء لأدهم العبودي أنموذجا - جديد, صالح (My University, 2014)
ا دي) 1 ا 2 أدھ *4 وا 5 ء 7 و8 ا ھ 9 ( , روا *+ ا ! را # ه ا % م ھ () ,5F? ت ا G (< ز ا 5A أ H ذ *+ B,#<9 ، E7+ ((;< ا , د5= ت ا 7?(9 ز ا 5A أ B CD وا ول ;Q <R .P,#; ا #(? ر ا F? B دي، 5= رس ا # ل ا *+ MN5O) *9 ،ا ,#(? ت ا A ر (< وا B7! ?9 57W ، , وا 5 ا *+ د 5= وا ا B7A VU ا#9 ت ا O; 5EFQ أن ?9! ل درا TU B ن D< ث وا #; A O1)5 7?() و 7? ز 7?() ره 19 A ، ا B 2 ?) *9 ا 4 ظ ا 5R ذ ],5^9 ا 7^7R د، و 5= وا ا B7A <4 ( ا NT ق 5O9 ا H %R ?9! ت درا O; B ت، و 7[\C وا . 74 وا 5 ا 7 < ا *+ <E?7A V[^ وا
Keywords: P,#; ا #(? دي، ا 5= رس ا # ، ا ,#(? ت ا A ر (< ، ا , د5= ت ا 7?(9 ، ا : ا _7) ^< ت ا < D